Generation of an isogenic series of genome-edited hiPSC lines with the BAG3P209L-mutation for modeling myofibrillar myopathy 6 - Isabelle Riße; Kerstin Filippi; Martin Wiemann; Bernd K. Fleischmann; Michael Hesse (Stem Cell Research)
BAG3 contributes to the maintenance of proteostasis through chaperone-assisted selective autophagy. This function is impaired by a single amino acid exchange (P209L) in the protein, which causes myofibrillar myopathy-6 (MFM6). This disease manifests as severe skeletal muscle weakness, neuropathy and restrictive cardiomyopathy. We generated an isogenic series of heterozygous and homozygous genome-edited human induced pluripotent stem cell (hiPSC) lines with the BAG3P209L-mutation and its control. For quality control, we tested the pluripotency of these hiPSC lines and their ability to differentiate into the three germ layers. Generation of these cell lines enables the analysis of cellular pathomechanisms of BAG3P209L-related MFM6.